OF COMPRESSIVE DISTRIBUTIONAL LOAD OF INTERVERTEBRAL DISC L4-L5 BY MEAND OFPHOTOELASTICITY (Fiep Bulletin - online, 2013)
The cells of the intervertebral disc are sensitive to mechanical involvements, being directly influenced by the hydrostatic pressure and compressive loads. The intervertebral disc is capable of distributing and attenuating these compressive loads between the adjacent vertebrae due to its viscoelastic properties. The photoelasticity has been used in researches to determine the distribution of stress in structural systems, thus it allows a qualitative and quantitative analysis by optic elements. It can be used in any state of stress, however, it is more easily used in a plane state. In this research, this technique has been used with the objective of analyzing and comparing the internal stress generated in the intervertebral disc L4-L5 put under efforts of compression. To perform the photoelastic analysis eight photoelastic models have been made and divided in two groups, the first represented by the central sagittal cut of the vertebral body L4-L5 and the second by the lateral cut of these vertebral bodies. The vertebral bodies were used to obtain the geometry of the intervertebral discs. The simulation was performed using a transmission polariscope with a load of 2.3 Kgf. The fringe orders were evaluated according to the contour of the intervertebral discs, using the Tardy compensation method. In all analysed models the shear stress has been determined. The results show that the posterior region of the disc of both models presented more concentration of stress, followed by the medium and anterior region. Therefore, this technique is very efficient, thus, through a quantitative and qualitative analysis it was possible to analyze the intervertebral disc, verifying which region is the most critical and susceptible to pathologies such as the disc degeneration and the disc hernia.
Keywords: L4-L5 Intervertebral disc; Biomechanics; Photoelasticity